The Evolution of Prosocial and Antisocial Competitive Behavior and the Emergence of Prosocial and Antisocial Leadership Styles - Gilbert, Paul; Basran, Jaskaran (Frontiers in Psychology, 2019)
.Evolutionary analysis focuses on how genes build organisms with different strategies for engaging and solving life’s challenges of survival and reproduction. One of those challenges is competing with conspecifics for limited resources including reproductive opportunities. This article will suggest that there is now good evidence for considering two dimensions of social competition. First, we will label antisocial strategies, to the extent that they tend to be self-focused, threat sensitive and aggressive, as well as using tactics of bulling, threatening, intimidating or even injuring/killing competitors. Their strategic goal is to stimulate fear-inhibition, flight or submissive compliance in subordinates. Such strategies turn off and inhibit care and affiliative social interactions and motivation and they can be enacted by parents, teachers and leaders. The social signals emitted stimulate various aspects of threat processing in recipients, create stressful and highly stratified groups with a range of detrimental psychological and physiological effects. Second, in contrast, prosocial strategies seek to create relaxed and secure social interactions that enable sharing, cooperative and mutually supportive and beneficial relationships. The friendly and low/no threat social signals emitted in friendly cooperative and affiliative relationships stimulate physiological systems (e.g., oxytocin, the vagus parasympathetic system) that down regulates threat processing, enhances the immune system, facilitates frontal cortical processes and general wellbeing. This article reviews the literature pertaining to the evidence for these two dimensions of social engagement.